Qualification of Administrative Practices as a Source for Turkish Tax Law - Mehmet Alpertunga Avci (Maliye Çalışmaları Dergisi)
In considering the relationship between positive and normative law, one must determine whether customs, one of the grounds of written law and administrative practices, and the manifestations of customs in practice, would be accepted as a source of law. Because, for example, an uncodified custom could not be a source of tax law, it would be impossible to take taxational action based solely on custom as the underlying principle of the legality of taxes. Nevertheless, it is apparent that legally codified customs will be the source of tax law. However, it is less certain whether the administrative practices that become visible when a law leaves enforcement to the tax administration’s discretion could be considered a similar legal source. The close relationship between tax and administrative law could be taken advantage of to overcome this uncertainty on tax-related administrative practices since most of the concepts and principles of tax law are built upon the theories underlying administrative law. This study aims to examine and reveal the potential of administrative practices as a legal source in Turkish Tax Law. Methodologically, the paper focuses on administrative law doctrine on custom and administrative practices and the Constitutional Court and Council of State’s decisions referring to the principle of legal security. Consequently, the article concludes that we should regard administrative practices, left to the administration’s discretion by the law, as a legal source of tax law to provide legal stability, certainty, and predictability. Such reliance will also protect acquired rights and meet fair expectations on the condition of any actions taken not being against the law.